The Relationship Between Foreign Direct Investment and Economic Growth: A Bibliometric Analysis - Lambekova, A.N.; Akbayev, Е.Т.; Myrzhykbayeva, А.B.; Berdikhojayeva, М.S.; Abayev, А.А. (BUKETOV BUSINESS REVIEW, 2024)
Object: To carry out a bibliometric analysis of the relationship between direct foreign investment and economic development, which has been studied for a long time in the economic literature and is of special importance for the economic and social development of any country. Methods: 4457 publications from the Scopus database were used for the analysis. The main tool of the work was the VOSViewer program, designed for data visualization and cluster analysis. Publications containing the keywords "direct foreign investment" and "economic growth" were selected as the subject of the study, which allowed to cover various temporal and regional aspects. Results: The analysis showed a high degree of correlation between FDI and economic growth. Cluster analysis demonstrated that both terms form the largest cluster, which indicates a strong correlation between them. In recent years, the focus of research has shifted to the ecological aspect related to the impact of PII. If earlier the main attention was paid to economic indicators, then modern studies increasingly consider such topics as carbon emissions and sustainable development. Conclusion: The obtained results confirm the important role of FDI in stimulating economic growth and improving the environmental situation. Further research into the impact of FDI on environmental aspects of growth and assessment of the impact of public investment on this process is recommended.